Investigating the process of shrinkage depression formation at the combined radial-backward extrusion of parts with a flange - Hrudkina, Natalia; Aliieva, Leila; Abhari, Payman; Markov, Oleg; Sukhovirska, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2019)
The possibilities of using an energy method to forecast defect formation in the form of shrinkage depression in the combined extrusion processes have been investigated. We have proposed a mathematical model of the combined radial-reverse extrusion process of hollow details with a flange, taking into consideration the degeneration of the trapezoidal module into a rectangular one. Separate stages in the deformation process have been defined, depending on the magnitude of the active tool stroke compared with the thickness of the bottom of the cup. We have devised a generalized estimation scheme for the process of combined radial-reverse extrusion of parts with a flange taking into consideration the final stage of deformation (Hbottom<h1). The magnitude of the reduced pressure of deformation has been derived as a function of the geometric, technological, and kinematic parameters of the extrusion process. A role of the kinematic parameter of the process belongs to a relative speed of metal flow in the vertical direction (filling the cup’s wall at the inverse flow of metal). The magnitude for the reduced pressure of deformation has been optimized based on this parameter. We have analyzed the character of change in the optimum magnitude of a relative speed of metal flow in the vertical direction in the course of the process. The differences have been established in the derived dependences of a given kinematic parameter for the process with the formation of shrinkage depression in the bottom part of a component and without defect formation. It has been substantiated that the use of combined extrusion in the manufacture of hollow parts with a flange, when compared with the application of simple schemes of deformation, improves the technological capabilities of the process. We have proven that the technologies for introducing combined extrusion had not been sufficiently studied and there is a lack of recommendations on predicting the formation of a defect in the form of shrinkage depression. The estimation scheme has been proposed for the radial-reverse extrusion process, taking into consideration the emergence of shrinkage depression at the final stage of deformation. We have modeled the process of combined extrusion of hollow parts with a flange and established the influence of friction conditions on the time of the emergence of shrinkage depression in the bottom part of a component. It has been confirmed that the proposed generalized estimation scheme makes it possible to predicting the occurrence of a defect in the form of shrinkage depression at all stages and under different technological conditions for a deformation process. Obtaining a preliminary assessment, based on it, of possible defect formation would facilitate the development of appropriate technological recommendations to avoid defects of this type